Роль Української греко-католицької церкви в допомозі голодуючим УРСР у 1932–1933 роках - Кіт, В. (Архіви України, 2008)
The author examines the role of the leaders of Ukrainian Greek-Catholic Church, first and foremost, the archdiocese and A. Sheptyts’kyi with regard to the European communities’ involvement in the activities aimed at putting an end to the genocide against Ukrainian people and dissemination of information about the 1932–1933 Famine in Ukraine on international level.